Cancer risks in a historical UK cohort of benzene exposed workers. - Sorahan, T; Kinlen, L; Doll, R (2005)
AIMS: To examine mortality from different causes and cancer incidence among a cohort of benzene workers in England and Wales. METHODS: A cohort of 5514 workers who had been occupationally exposed to benzene in 1966/67 or earlier was assembled by the former Factory Inspectorate and the Medical Research Council from details provided by 233 employers in England and Wales. The cohort was followed up for mortality (1968-2002) and cancer registrations (1971-2001). National mortality rates and cancer registration (incidence) rates were used to calculate standardised mortality ratios and standardised registration ratios. RESULTS: Mortality was close to expectation for all causes and significantly increased for cancer of the lip, cancer of the lung and bronchus, secondary and unspecified cancers, acute non-lymphocytic leukaemia (ANLL), and all neoplasms. Significant deficits were shown for three non-malignant categories (mental disorders, diseases of the digestive system, accidents). SMRs for other leukaemia, lymphomas, and multiple myeloma were close to or below expectation. There was some evidence of under-ascertainment of cancer registrations, although significantly increased SRRs were shown for lung cancer and cancer of the pleura (mesothelioma). CONCLUSIONS: Many study subjects would have been exposed to carcinogens other than benzene (for example, asbestos, rubber industry fumes, foundry fumes, polycyclic aromatic hydrocarbons), and the excesses of lung cancer and mesothelioma are likely to reflect exposures to these other carcinogens. The carcinogenic effects of benzene exposure on the lymphohaematopoietic system were limited to ANLL.